352 PROGNOSTIC VALUE OF THE TPEAK-TEND INTERVAL FOR IN-HOSPITAL SUBACUTE VENTRICULAR ARRHYTHMIAS IN TAKOTSUBO SYNDROME. (15th December 2022) - Rosa, Giulio La; Pelargonio, Gemma; Lucia Narducci, Maria; Pinnacchio, Gaetano; Bencardino, Gianluigi; Perna, Francesco; Follesa, Federico; Galiuto, Leonarda; Crea, Filippo
Abstract: Introduction and objectives: The clinical value of ECG repolarization parameters associated with ventricular arrhythmias (VAs) in Takotsubo syndrome is still under debate. We aimed to evaluate ECG predictors of subacute VAs, defined as those occurring after the first 48 hours from admission. Methods: This is a single-center observational study enrolling patients admitted to the Cardiology Department between 2012 and 2018 with confirmed diagnosis of Takotsubo syndrome. Data collection included a 12-lead ECG on admission and at 48 hours, continuous telemetry monitoring, blood testing, transthoracic echocardiography and coronary angiography during hospitalization. VAs events were defined as: premature ventricular contractions ≥2000 within a 24-hour window of telemetry monitoring, ventricular fibrillation, sustained ventricular tachycardia (VT), polymorphic VT and non-sustained VT. Results: A total of 87 patients (age 72±12 years old) were enrolled. During an average of 16±14 days of hospitalization, subacute VAs were documented in 22 patients (25%) after 127±75 hours from admission. Subacute VAs were associated with an increased in-hospital mortality (p=0.030). The corrected global (mean of the 12-lead ECG values) Tpeak-Tend interval at 48 hours from admission was an independent predictor of subacute VAs. The corrected global Tpeak-Tend was statistically superior to the standard corrected QT interval to predict subacute VAs (Z test, p=0.040). A cut-off of 108 msec for the corrected global Tpeak-Tend yielded a 71% sensitivity and 72% specificity for subacute VAs. Conclusions: In patients with Takotsubo syndrome subacute VAs are associated with repolarization alterations that can be identified on the conventional ECG using the Tpeak-Tend interval.